2021
DOI: 10.1002/csc2.20420
|View full text |Cite
|
Sign up to set email alerts
|

Assessing drought resistance in seashore paspalum genotypes using leaf gas exchange, osmotic adjustment, and rooting characteristics

Abstract: The objective of this study was to compare drought resistance in a range of seashore paspalum (Paspalum vaginatum Sw.) genotypes and identify associated morphological and physiological traits. Fifteen genotypes were grown in growth chamber conditions and exposed to well‐watered and drought‐stress treatments. Genotypes ‘Seaisle1’ and PI647891 were consistent top performers, whereas ‘Seastar’ and PI614680 performed poorly as measured by turf quality, percentage green cover, and relative water content when expose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 60 publications
2
5
0
Order By: Relevance
“…These findings are consistent with previous studies on which they found that biochar increased plant growth under drought conditions [21,22]. Katuwal et al [23] reported that under drought, seashore paspalum limited the gas-exchange process by maintaining its stomatal conductance and closing its stomata. Furthermore, Pompeiano et al [8] found that seashore paspalum and bermudagrass could increase roots even in salinity intermediate stress.…”
Section: Discussionsupporting
confidence: 92%
“…These findings are consistent with previous studies on which they found that biochar increased plant growth under drought conditions [21,22]. Katuwal et al [23] reported that under drought, seashore paspalum limited the gas-exchange process by maintaining its stomatal conductance and closing its stomata. Furthermore, Pompeiano et al [8] found that seashore paspalum and bermudagrass could increase roots even in salinity intermediate stress.…”
Section: Discussionsupporting
confidence: 92%
“…In accordance with our findings, similar studies showed that adding biochar improved photosynthesis and stomatal conductance even in harsh conditions [1,20]. Actually, in the absence of biochar [2] discovered that plants can survive without organic amendments, in addition, adhere to stringent stomatal limitations, which mostly led to a reduction in transpiration E and CO2 supply for photosynthetic activity escape [16] reported that under drought, seashore paspalum limited IOP Publishing doi:10.1088/1755-1315/1090/1/012017 5 the gas exchange process by maintaining its stomatal conductance and closing its stomata. As an adjustment to tough conditions, P. vaginatum tended to close its stomata as an adjustment mode to avoid the water escape.…”
Section: Effect Of Peanut Hull Biochar On Physiological Responses Of ...supporting
confidence: 90%
“…High morphological variability becomes a desire for germplasm conservation and parents' selection in breeding programs (Khadivi-Khub et al 2014). Assessment of the morphology characteristics of seashore paspalum indicates a potential to improve resistance in future turfgrass cultivars (Katuwal et al 2021). Therefore, the leaf size of turfgrass affects evapotranspiration and is related to water consumption (Xu et al 2013).…”
Section: Introductionmentioning
confidence: 99%